The Neotropical species of Clistopyga (Hymenoptera, Ichneumonidae, Pimplinae). Part II: the C. isayae species group, with the description of seven new species - Palacio, Edgard; Bordera, Santiago; Sääksjärvi, Ilari E.; Díaz, Francisco (Zootaxa, 2018)
The New World Clistopyga isayae species group is revised. Seven species are described as new: C. crassicaudata sp. nov., C. isayae sp. nov., C. kalima sp. nov., C. nigriventris sp. nov., C. panchei sp. nov., C. splendida sp. nov. and C. taironae sp. nov. An illustrated identification key to all species of the group is provided. The Clistopyga isayae species group is composed entirely of previously undescribed species mainly from Andean forests of tropical South America.